Comparison of the mechanical properties and depth of cure of bulk-fill and bioactive composite resins - Ríos-Angulo, Carlos Manuel (2025)
Objective: To compare in vitro the mechanical properties and depth of cure of bioactive bulk-fill resins versus bulk-fill composite resins. Materials and methods: An in vitro experimental study was conducted with 48 blocks of three types of resin. Each block received a load of 500 g for 30 seconds and was photopolymerized with a VALO® Cordless-Ultradent unit (1500 mW/cm2) for 4 seconds. Microhardness was evaluated using the Vickers hardness test, employing a calibrated LG® HV-1000 hardness tester. For statistical analysis, the Student's t-test and the non-parametric Kruskal-Wallis test were applied, considering statistical significance if p < 0.05. Results: The bioactive resin Beautifil® Bulk (BB) showed the highest microhardness, reaching a mean value of 55.1 VH (p < 0.01), followed by the resins Tetric® N-Ceram Bulk Fill (TNCBF) with 44.9 VH and Tetric® N-Flow Bulk Fill (TNFBF) with 28.8 VH. The TNFBF bulk-fill resin showed the highest compressive strength, with a mean of 222.4 MPa (p < 0.01), compared to 173.5 MPa for the TNCBF moldable resin and 129.7 MPa for the flowable BB resin. All three resins achieved a homogeneous mean curing depth of 4.0 mm (p > 0.05). Conclusions: The BB bioactive resin showed greater microhardness compared to moldable and flowable bulk-fill resins, while the TNFBF flowable bulk-fill resin showed the highest compressive strength. All three resins had similar values in terms of curing depth.